Kebersyukuran, persepsi dukungan sosial, dan resiliensi pelajar di masa pembelajaran jarak jauh (PJJ) pandemi COVID-19 - Fitroh, Nurul; Mansoer, Winarini Wilman D. (Konsorsium Psikologi Ilmiah Nusantara, 2024)
The COVID-19 pandemic changed many aspects of life, including learning process. Distance learning has been implemented as a response to the pandemic. These changes have a psychological impact on students. This study aims to explore the role of gratitude as a mediator in the relationship between social support and resiliency among students during distance learning. This study used quantitative method to 42 students (M=21,5). The study found that, while gratitude is not meaningful mediating variabel accounting for the relationship between social support and resilience, perceived social support predicts higher levels of resilience and gratitude among students participating in distance learning. While few participants reported that they adjusted well with the shift of learning mode, common challenges faced by participants which necessitates resilience in distance learning include: less enthusiasm in learning due to limited social interaction, poor time management, and exhaustion due to prolong exposure to screen.